THE IMPACT OF BIOLOGY TEACHING BASED UPON MULTIPLE INTELLIGENCE THEORY ON ACADEMIC ACHIEVEMENT: A META-ANALYSIS STUDY - Hande Çetinkıl; Hikmet Katırcıoğlu; Yeliz Yalçın (Informascope, 2017)
The purpose of this research is to synthesize the results obtained from experimental studies on the academic achievement of students based on the multiple intelligence theory in biology and to reveal the effect of different characteristics in the studies by meta-analysis method. In this study, the magnitude of the impact of 14 studies on the academic achievement of students of biology education based on multiple intelligence theory was analyzed. As a result of the meta-analysis, it was determined that teaching based on multiple intelligence theory affects academic achievement in a positive direction compared to the traditional teaching method and the effect size value was 1.308. This value is quite high compared by Cohen's scale. In the meta-analysis study duration of application, sample size, publication type variables were analyzed. It is seen that the highest effect values are in the graduate thesis (dg-t=1,549), 5-8 weeks (d5-8 weeks=2,007) and medium sample sizes (dmedium=1,427) (51n 75) according to the determined criteria. Keywords: Multiple Intelligence Theory, Biology Teaching, Meta-Analysis, Academic Achievement